Rural and urban dynamics and poverty: Evidence from China and India - Fan, Shenggen; Chan-Kang, Connie; Mukherjee, Anit (International Food Policy Research Institute, 2005)
This paper explores the dynamic relationship between the rural and urban sectors and the consequent impact on poverty in China and India, both of which followed aggressive urban industrialization paths in the mid-twentieth century. The bulk of the population of each of these countries still resides in the rural areas where the incidence of poverty is greatest....Empirical evidence demonstrates that public investment in the rural sector—particularly in rural infrastructure as well as in agricultural research and development, and education—will yield the largest returns in terms of both growth and poverty reduction. In the poorest areas, such as western China and eastern India, the poverty reduction effect from these investments is particularly high.